Myocardial infarction due to septic thromboembolism in chronic rheumatic heart disease - Suneel Rachagiri; Aravind Sekar; Saurabh Mehrotra; Uma Nahar Saikia (University of São Paulo, 2023)
Chronic rheumatic heart disease (RHD) is the most troublesome complication of rheumatic fever. Extensive valvular scarring and ventricular remodeling due to pressure and volume overload occur in chronic RHD. Deformed valves are at potential risk for developing infective endocarditis (IE) with further systemic embolism. We hereby describe a case of a patient diagnosed with chronic rheumatic heart disease and severe ventricular dysfunction, planned for aortic valve replacement. The patient developed septic shock during a hospital stay. The autopsy revealed infective endocarditis in the aortic valve with septic thromboembolism in the peripheral branches of the coronary artery and early multifocal myocardial infarction changes.